Prosocial behavior of Muslim and Christian communities in Public Space - Rukmina Gonibala, Musdalifah Dachrud; Wekke, Ismail Suardi (Opción, 2019)
The article would like to investigate the prosocial behavior of Muslim and Christian communities in public space that employed qualitative method with ethnography approach and focused on the community of Jalan Roda in Manado. The findings showed that the prosocial behavior shown by citizens in Jalan Roda community succeeds in forming social relations between individuals very well, where the strength is determined by how the citizens in it do their interactions among them. In conclusion, both motivation and its driving factors lie in the nature of collectivism.